Aging, health, and public policy demographic and economic perspectives - Waite Linda J (New York Population Council, 2004)
This volume includes a variety of disciplinary perspective ranging from demography to economics to epidemiology. It has been divided into 4 major sections viz. History, biology and disease; Health and socio-economic status; aging, Work and public policy
A supplement to Population and Development Review, vol 30, 2004
Keywords: Age distribution (Demography)-economic aspects; Economic conditions; Government policy; Health and hygiene; Old age assistance-forecasting; Older people; Social conditions